ISOLASI DAN UJI ANTAGONIS BAKTERI ENDOFIT DARI TANAMAN BAWANG MERAH (Allium ascalonicum L.) TERHADAP JAMURAlternaria porri Ellis Cif. - Agus Pitasari; Muhammad Ali (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
The research aims to isolate and to observe the antagonicity of endophytic bacteria from onion plant to Alternaria porri Ellis Cif. The research has been conducted at Plant Pathology Laboratory, Agriculture Faculty, University of Riau from April until June 2017. The research used explorational method (isolation and purification of the bacteria from red onion), experimental method (antagonicity test of bacteria endophytic from red onion plant and A. porri) and observation methods (hypersensitive test). Data collected from step 1 and 3 were analyzed descriptively. Step 2 used analysis of variance. The mean treatments were compared with Duncan’s new multiple range test at 5% level. Result of the research showed that there were 9 different bacterial isolated based on their color and shape. There were five highest antagonicity bacteria root-1 (54,00%), leaf-1 (46,00%), bulb-1 (44,00%), leaf-3 (42,00%) and bulb-3 (38,00%). The five bacteria are not hypersensitive due to the absence of the necrosis on injected tobacco leaf. Key words: Endophytic bacteria, onion plants, antagonicity, A. porri